2021
DOI: 10.1038/s41598-021-85681-w
|View full text |Cite
|
Sign up to set email alerts
|

Buspirone alleviates anxiety, depression, and colitis; and modulates gut microbiota in mice

Abstract: Gut microbiota regulate the neurodevelopmental processes and brain functions through the regulation of the microbiota–gut interaction and gut–brain communication. Buspirone, an agonist for serotonin 5-HT1A receptors, is used for the treatment of anxiety/depression. Therefore, to understand the gut microbiota-mediated mechanism of buspirone on anxiety/depression, we examined its effect on the immobilization stress (IS) or Escherichia coli K1 (EC)-induced anxiety/depression in mice. Oral or intraperitoneal admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 39 publications
0
14
0
2
Order By: Relevance
“…They concluded that buspirone, by inhibiting inflammatory factors such as; TNF-α, IL-1β, and IL-6 reduced inflammation [43]. Another animal study in 2021 showed that buspirone inhibited inflammation and reduced colitis by inhibiting myeloperoxidase and NF-κB activation [14]. Buspirone can be effective in treating various inflammatory diseases such as colitis, psoriasis, and dermatitis that have elevated levels of TNF-α and other inflammatory factors [44].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They concluded that buspirone, by inhibiting inflammatory factors such as; TNF-α, IL-1β, and IL-6 reduced inflammation [43]. Another animal study in 2021 showed that buspirone inhibited inflammation and reduced colitis by inhibiting myeloperoxidase and NF-κB activation [14]. Buspirone can be effective in treating various inflammatory diseases such as colitis, psoriasis, and dermatitis that have elevated levels of TNF-α and other inflammatory factors [44].…”
Section: Discussionmentioning
confidence: 99%
“…Our study shows that buspirone reduces MPO expression and has lucrative effects in treating acute colitis 38 . Buspirone is an oral anti-anxiety drug mainly used to treat anxiety disorders, especially generalized anxiety disorder 14 . Our study is in accordance with the anti-inflammatory effect of buspirone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, alterations in the intestinal flora caused by psychotropic drugs, including fluoxetine, AMI, and buspirone, have been shown in animal models (9,10). Alterations in the intestinal flora may be beneficial in improving depression and anxiety (10). It has not been shown how the oral flora is altered by the administration of psychotropic drugs.…”
mentioning
confidence: 99%